Relationship between self-reported functional stabilityand peroneal muscle structure in individuals with chronicankle instability - (:unkn) unknown (My University, 2020)
Purpose: Chronic ankle instability is characterized by repeated ankle sprains. Peroneal muscles are important for control of theankle and have been evaluated using electromyographic analyses, but there has been lack of study about any relationshipbetween the peroneal muscle structure and self-reported function after ankle sprains. Therefore, this study aimed to investigatethe relationship between self-reported functional stability and peroneal muscle structure in chronic ankle instability.Methods: Thirty subjects aged between 18-45 years and reporting chronic ankle instability were evaluated. Participantscompleted the Cumberland Ankle Instability Tool questionnaire to determine ankle stability experience. Structural analysis ofthe peroneal muscles was performed using musculoskeletal ultrasound scanning. Cross sectional area and thickness ofperoneal longus and brevis were scanned.Results: The mean Cumberland Ankle Instability Tool score of subjects was 15.40±6.23. A statistically significant positivemoderate correlation was found between stability scores and total cross-sectional area of peroneal muscles (r=0.405,p=0.027). In another words; subjects with higher levels of self-reported ankle stability had larger peroneal cross-sectional area.Conclusion: The subjects with chronic ankle instability who had larger peroneal cross-sectional area may have greater peronealstrength. Thereafter, this group may have better ankle stability than those with perceived low ankle stability. This potential for astructural relationship associated with improved stability may be relevant to physiotherapists and rehabilitation programmes.Further research may focus on other muscular structures around the ankle joint in chronic ankle instability.

Amaç: Kronik ayak bileği instabilitesi tekrarlayan ayak bileği burkulmaları ile karakterize edilir. Peroneal kaslar ayak bileğinin kontrolü için önemlidir ve elektromyografik analizler kullanılarak değerlendirilir ancak peroneal kas yapısı ile ayak bileği burkulmalarından sonra bildirilen subjektif fonksiyon arasındaki ilişki hakkında yeterli çalışma bulunmamaktadır. Bu nedenle, bu çalışmanın amacı, kronik ayak bileği instabilitesinde birey tarafından beyan edilen fonksiyonel stabilite ile peroneal kas yapısı arasındaki ilişkiyi araştırmaktı. Yöntem: Çalışma kapsamında 18-45 yaş aralığında, kronik ayak bileği instabilitesi olan 30 birey değerlendirildi. Olgular ayak bileği stabilite deneyiminin belirlenmesi için Cumberland Ayak Bileği Instabilite Ölçeği’ni doldurdu. Peroneal kasların yapısal analizi kas iskelet sistemi ultrason görüntüleme yöntemiyle gerçekleştirildi. Peroneus longus ve brevisin kesit alanı ve kalınlığı görüntülendi. Bulgular: Olguların Cumberland Ayak Bileği İnstabilite Ölçeği skoru ortalama 15,40±6,23 idi. Stabilite skorları ile peroneal kasların kesit alanı arasında istatistiksel olarak anlamlı pozitif ve orta düzeyde bir korelasyon saptandı (r=0,405; p=0,027). Diğer bir deyişle; subjektif ayak bileği stabilitesi yüksek olan olgular daha geniş peroneal kesit alanına sahipti. Sonuç: Daha geniş peroneal kesit alanı olan kronik ayak bileği instabilitesi olan olgular daha yüksek peroneal kuvvete sahip olabilir. Bu durumda, bu grup düşük seviyede algılanan ayak bileği stabilitesi olan olgulardan daha iyi ayak bileği stabilitesine sahip olabilir. Geliştirilmiş stabilite ile ilgili bu yapısal ilişki potansiyeli fizyoterapistleri ve rehabilitasyon programlarını ilgilendirebilir. Daha fazla araştırma kronik ayak bileği instabilitesinde ayak bileği eklemi çevresindeki diğer kas yapılarına odaklanabilir.
Kronik ayak bileği instabilitesi olan bireylerde subjektif fonksiyonel stabilite ile peroneal kas yapısı arasındaki ilişki